Better oral hygiene is associated with a reduced risk of cataract: A nationwide cohort study - Park, Jung-Hyun; Lee, Heajung; Kim, Jin-Woo; Song, Tae-Jin (Frontiers in Medicine, 2023)
Objective: To investigate the association of oral health status and oral hygiene behaviors with cataract occurrence longitudinally Materials and Methods: Based on the National Health Screening cohort database of Korea, participants who underwent oral health screening by dentists in 2003 were included. Cataract was defined as two or more claims of disease classification for the International Classification of Diseases-10 (E10.34, E11.34, E12.34, E13.34, E14.34, H25, and H26) with cataract specific treatment or surgery procedure claim codes. The occurrence of cataract was analyzed with Cox proportional hazard model according to the presence of periodontitis and oral health examination findings, including missing teeth, caries, tooth brushing, and dental scaling. Results: Overall, 103,619 subjects were included. During a median follow-up of 12.2 years, cataract developed in 12,114 (11.7%) participants. Poor oral health status such as the presence of periodontitis (adjusted hazard ratio [HR] 1.077, 95% CI [confidence interval] 0.989–1.173, p=0.088) and increased number of missing teeth (adjusted HR = 1.744, 95% CI = 1.554–1.958, p< 0.001) was associated with the increased cataract risk. Better oral hygiene behaviors such as increased frequency of tooth brushing (adjusted HR = 0.835, 95% CI = 0.790–0.881, p< 0.001) and performed dental scaling within 1 year (adjusted HR = 0.900, 95% CI = 0.859–0.943, p< 0.001) were negatively associated with cataract occurrence. Conclusion: Periodontitis and increased number of missing teeth may increase the risk of cataract. However, maintaining good oral hygiene through tooth brushing and dental scaling may reduce the risk of future cataract occurrence. Further studies should be performed to confirm the association between chronic oral inflammation and cataract.